2016
DOI: 10.1002/hfm.20662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grip Curvature and Hand Anthropometry for the Unimanual Operation of Touchscreen Handheld Devices

Abstract: This study evaluated the effect of hand anthropometry and screen curvatures of handheld devices on hand comfort during single-hand touchscreen operations. By employing both subjective ratings and electromyography methods, the comfort level was measured using three mock-up devices with different curvatures; one was flat and the others had curvatures of 400 R and 100 R. The participants were classified by sizes and shapes of their preferred hand based on factor analysis results. In this study, 26 adults in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This has been reported before in studies showing altered motor control and muscle activation (during non-MTSD tasks) among people with neck pain [ 78 80 ]. Different hand sizes and shapes may also influence musculoskeletal symptoms or exposures at the distal upper extremity, as one study indicated their significant effect on muscle activity of the fingers and thumb during MTSD use [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has been reported before in studies showing altered motor control and muscle activation (during non-MTSD tasks) among people with neck pain [ 78 80 ]. Different hand sizes and shapes may also influence musculoskeletal symptoms or exposures at the distal upper extremity, as one study indicated their significant effect on muscle activity of the fingers and thumb during MTSD use [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…They compared hand length, hand width and both measurements with other populations such as those of Western Europe, West India, India (Punjab), Hong Kong China, the UK, Japan, Africa/Sudan, Sri Lanka, Sweden and Egypt. Ahn et al (2016) studied the effect of grip curvature and hand anthropometry for the unimanual operation of touch screen handheld devices. Irwin and Radwin (2008) estimated the internal biomechanical loads of the hand from external loads and finger lengths that were themselves estimated from measured hand length and breadth.…”
Section: Related Workmentioning
confidence: 99%
“…By the knowledge of these authors, no validated objective measurement for grip comfort has been reported in relevant literature. Neither Ahn, Kwon, Bahn, Yun, and Yu (2016) nor Lee et al (2016) discovered significant associations between muscle activities and perceived discomfort, indicating muscle activities are insufficient for explaining physical discomfort. It is thus worthwhile to discover new objective measurements capable of effectively explaining grip comfort.…”
Section: Discussionmentioning
confidence: 85%